Increasing Black Employees’ Social Identity Affirmation and Organizational Involvement: Reducing Social Uncertainty Through Organizational and Individual Strategies - Wang, Cynthia; Ku, Gillian; Smith, Alexis Nicole; Edwards, Bryan; Scott, Edward; Galinsky, Adam D. (Organization Science, 2025)
Despite the psychological benefits of authenticity, Black employees within predominantly White organizations often face the dilemma of whether to downplay versus highlight their social identity. Our research introduces social uncertainty as a unifying lens to understand the reluctance of these employees to express their social identity. Highlighting the central role of social uncertainty also helps identify novel factors at both the organizational level (authenticity climates) and individual level (perspective-taking) that can encourage Black employees to engage in social identity affirmation—authentic expressions of the positive aspects of their social identity. To test our hypotheses, we conducted two survey studies, two experiments, qualitative interviews, as well as coded text responses to our experimental prompts. Across our studies, authenticity climates were associated with greater social identity affirmation by Black employees, and this relationship was strengthened when these employees engaged in perspective-taking. Consistent with our theorizing, social certainty mediated these direct and moderated effects. In addition, social identity affirmation increased Black employees’ organizational involvement. Our experimental studies offer causal evidence for the roles of both authenticity climates and Black employees’ perspective-taking, our qualitative interviews vividly illuminate our hypotheses, and our text response analyses provide insight into how authenticity climates operate. Overall, the current research highlights how organizations can help Black employees feel comfortable emphasizing and expressing their true selves by increasing their social certainty. These findings also have direct implications for organizational leaders, providing them with actionable strategies to create more inclusive environments. Funding: The research was supported by Northwestern University and Oklahoma State University. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2020.14659 .